2014
DOI: 10.1017/jfm.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on unstable surfaces of oblique detonations

Abstract: In this study, the onset of cellular structure on oblique detonation surfaces is investigated numerically using a one-step irreversible Arrhenius reaction kinetic model. Two types of oblique detonations are observed from the simulations. One is weakly unstable characterized by the existence of a planar surface, and the other is strongly unstable characterized by the immediate formation of the cellular structure. It is found that a high degree of overdrive suppresses the formation of cellular structures as conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 45 publications
3
51
0
1
Order By: Relevance
“…Indeed from both experiments [5] and numerical simulations [9][10][11][12][13][14], it was observed that the oblique detonation surface can be unstable with the generation of triple points and fine scale cellular unstable structures very similar to normal cellular detonation. Numerically, it was found by Choi et al [11] using mixtures of different activation energies that these unstable oblique detonation structures cannot be captured without sufficient numerical resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed from both experiments [5] and numerical simulations [9][10][11][12][13][14], it was observed that the oblique detonation surface can be unstable with the generation of triple points and fine scale cellular unstable structures very similar to normal cellular detonation. Numerically, it was found by Choi et al [11] using mixtures of different activation energies that these unstable oblique detonation structures cannot be captured without sufficient numerical resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al [8] studied these small scale structures and demonstrated the coupling relation between the shock and the combustion. Teng et al [9] found out the formation of triple points is hard in the case of high overdrive degree, but it derives from small disturbance and cannot be suppressed thoroughly. The other kind of small scale structures, which is similar to the detonation cell on the normal detonation surface, are also observed and discussed recently [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For the computation, the coordinate is rotated to the direction along the wedge surface. Hence, the Cartesian grid in the rectangular domain enclosed by the dashed line is aligned with the wedge surface, like our previous studies 6,7 .…”
Section: Numerical Model and Methodsmentioning
confidence: 95%
“…For instance, Li et al 3 revealed that the multi-dimensional oblique detonation structure consists of a non-reactive oblique shock, an induction region, a set of deflagration waves, and an oblique detonation surface. The instability of oblique detonation surface has been studied widely, demonstrating the cellular structure formation and evolution 4,5,6,7 . Another research direction is the oblique shock-to-detonation transition, which can be viewed as the initiation process of oblique detonation.…”
Section: Introductionmentioning
confidence: 99%